2017
DOI: 10.1111/odi.12737
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontitis and severe asthma in adults: A case–control study

Abstract: Association between periodontitis and severe asthma was observed. Further investigation is required to determine the direction of this relationship. It may be causal, but it may also be a consequence of the immunopathological process that characterizes asthma, or else, consequence of the medication used for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
0
20
0
3
Order By: Relevance
“…Of the total number of studies included in the review, 3 (Appendix S1) evaluated the relationship between periodontitis and respiratory diseases but, one had only crude association measurement between periodontitis and COPD (Chung et al, 2016), and in the other, two did not contain the association measurement or means to obtain it (Si et al, 2012;Terashima et al, 2017). Of the 10 remaining studies that presented the adjusted association measurement, only 3 investigations were included in the meta-analysis to generate the summary association measurement between periodontitis and asthma (Gomes-Filho et al, 2014;Khassawneh et al, 2019;Soledade-Marques et al, 2018). Four studies between periodontitis and COPD (Barros et al, 2013;Harland et al, 2018;Ledić et al, 2013;Takeuchi et al, 2019) covariables most frequently considered in the adjustment of the association measurements were age (92.31% of the studies), smoking habit (76.92%), body mass index (53.85%), sex (46.15%), schooling level (38.46%), and alcoholic beverage consumption (23.08%).…”
Section: General Characteristics and Quality Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the total number of studies included in the review, 3 (Appendix S1) evaluated the relationship between periodontitis and respiratory diseases but, one had only crude association measurement between periodontitis and COPD (Chung et al, 2016), and in the other, two did not contain the association measurement or means to obtain it (Si et al, 2012;Terashima et al, 2017). Of the 10 remaining studies that presented the adjusted association measurement, only 3 investigations were included in the meta-analysis to generate the summary association measurement between periodontitis and asthma (Gomes-Filho et al, 2014;Khassawneh et al, 2019;Soledade-Marques et al, 2018). Four studies between periodontitis and COPD (Barros et al, 2013;Harland et al, 2018;Ledić et al, 2013;Takeuchi et al, 2019) covariables most frequently considered in the adjustment of the association measurements were age (92.31% of the studies), smoking habit (76.92%), body mass index (53.85%), sex (46.15%), schooling level (38.46%), and alcoholic beverage consumption (23.08%).…”
Section: General Characteristics and Quality Of Studiesmentioning
confidence: 99%
“…Asthma is a chronic inflammatory disease affecting both young and old (Beasley et al, ). An increasing number of studies have observed an association with periodontal disease (Gomes‐Filho et al, ; Khassawneh, Alhabashneh, & Ibrahim, ; Soledade‐Marques et al, ). The same has been seen for chronic obstructive pulmonary diseases (COPD), a chronic condition comprised of both bronchitis and emphysema characterized by airflow obstruction due to increased chronic inflammatory response within the airway.…”
Section: Introductionmentioning
confidence: 99%
“…12 The minimum estimated sample size was 430, that is, 215 cases and 215 controls. Sample size was calculated by considering the exposure factor of periodontitis from a previous study involving cases of severe asthma, which found a 30.34% frequency in the case group versus 49.8% in the control group.…”
Section: Participantsmentioning
confidence: 99%
“…4 Severe asthma is characterized by the presence of daily symptoms necessitating the use of bronchodilators, incapacity, emergency hospital visits, repetitive use of systemic corticosteroids, and diminished pulmonary function. 5,7 Diseases caused by viral and bacterial infections, 7-10 as well as chronic diseases, such as periodontitis, 3,11,12 can provoke the exacerbation of bronchial inflammation, disrupted mucociliary transport, and increased mucus production, which can worsen asthma. 5,6 Several microorganisms have been related to the pathogenicity of asthma as these play an important role in respiratory disorders and can modulate the heterogeneity of this health condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation